Modern Nonparametric, Robust and Multivariate Methods Festschrift in Honour of Hannu Oja - Nordhausen, Klaus; Taskinen, Sara.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Written by leading experts in the field, this edited volume brings together the latest findings in the area of nonparametric, robust and multivariate statistical methods. The individual contributions cover a wide variety of topics ranging from univariate nonparametric methods to robust methods for complex data structures. Some examples from statistical signal processing are also given. The volume is dedicated to Hannu Oja on the occasion of his 65th birthday and is intended for researchers as well as PhD students with a good knowledge of statistics.
Foreword -- Preface -- Part I: Remarks About Hannu Oja$1 (Bs Career and Publications -- Part II: Univariate Nonparametric and Robust Methods -- Part III: Nonparametric and Robust Methods for Multivariate and Functional Data -- Part IV: Invariant Coordinate Selection and Related Methods.s
Keywords: Statistics; Statistics; Statistical Theory and Methods; Signal, Image and Speech Processing; Statistics for Engineering, Physics, Computer Science, Chemistry and Earth Sciences; Electronic books